The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1530/ec-16-0105
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effects of shikonin derivatives on human medullary thyroid carcinoma cells

Abstract: New treatment options are needed for medullary thyroid carcinoma (MTC), a highly metastasizing neuroendocrine tumor that is resistant to standard radiotherapy and chemotherapy. We show that the following shikonin derivatives inhibit cell proliferation and cell viability of the MTC cell line TT: acetylshikonin, β,β-dimethylacrylshikonin, shikonin and a petroleum ether extract of the roots of Onosma paniculata containing several shikonin derivatives. The unsubstituted shikonin derivative was found to be the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In previous investigations, we demonstrated that 1 also induced apoptosis caspase 3 dependently after 24 h [ 8 ]. The induction of apoptosis by shikonin derivatives was also reported in other types of cancer such as medullary thyroid carcinoma cells [ 6 ], human gastric cancer cells, and human breast cancer cells [ 38 , 39 ]. To confirm apoptosis induction, immunoblotting and flow cytometric experiments were performed.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In previous investigations, we demonstrated that 1 also induced apoptosis caspase 3 dependently after 24 h [ 8 ]. The induction of apoptosis by shikonin derivatives was also reported in other types of cancer such as medullary thyroid carcinoma cells [ 6 ], human gastric cancer cells, and human breast cancer cells [ 38 , 39 ]. To confirm apoptosis induction, immunoblotting and flow cytometric experiments were performed.…”
Section: Resultsmentioning
confidence: 80%
“…In previous studies, roots of O. paniculata were phytochemically and pharmacologically investigated and emerged as promising research objects [ 5 , 6 , 7 , 8 ]. We were able to isolate several shikonin derivatives and investigated their effects on various tumor cell lines including leukemia, medullary thyroid carcinoma, glioblastoma, colon cancer, breast cancer, and melanoma [ 5 , 6 , 7 , 8 ]. Overall, β , β -dimethylacrylshikonin ( 1 ) was the most cytotoxic compound of all isolated derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…erythrorhizon root (Gwon et al, 2012; Pietrosiuk et al, 2006; Zhao, Wu, Wu, Zhao, & Chen, 2016), exhibits various pharmacological activities including induction of autophagy, anti‐oxidative, anti‐inflammatory, anti‐proliferative, anti‐fertility, and anticancer effects (He, Li, Su, Huang, & Zhu, 2016; Pietrosiuk et al, 2006; Skrzypczak et al, 2015; Wu et al, 2011; Zeng, Zhu, & Su, 2018). Several studies have demonstrated that the compound inhibits growth of a variety of cancers, including colorectal, breast, liver, medullary thyroid carcinoma, pancreas, melanoma, and gastric cancers (Cho & Choi, 2015; Hasenoehrl et al, 2017; Kim, Lee, Park, & Choi, 2016; Kretschmer et al, 2012; Park et al, 2017; Vukic et al, 2017; Zeng, Liu, & Zhou, 2009). Mechanistically, acetylshikonin has been reported to act by down‐regulating NF‐κB, Bcl‐2 expression, and CYP2J2 activity, and the IL‐8/MMP axis, or by up‐regulating expression of haem oxygenase‐1 (Cho et al, 2018; Cho & Choi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As a major component of Zicao, shikonin exhibits anti-tumor activity [4,19] and has been reported to be less cytotoxic [20][21][22][23] and circumvent drug resistance [24] of various tumor cell lines. In the present study, we tested the effects of shikonin on K562 cells.…”
Section: Discussionmentioning
confidence: 99%